PENGARUH PERSEPSI KONSUMEN PADA STORE ATMOSPHERE TERHADAP IMPULSE BUYING MELALUI SHOPPING EMOTION PLEASURE - Dinda Prasetya Aurellia (Fakultas Ekonomi, Universitas Sanata Dharma Yogyakarta, 2019)
This study aimed to investigated the influence of consumers perceptions on store atmosphere toward impulse buying and shopping emotion pleasure. This study also investigated the mediating role of shopping emotion pleasure. By using accidental sampling technique, this study took 100 consumers of Mirota Babarsari Yogyakarta who were at least 17 years old. The data were obtained by using a structured questionnaires and analyzed by using Path Analysis via Regression. The results indicated that consumers perceptions on store atmosphere affected impulse buying, consumers perceptions on store atmosphere affected shopping emotion pleasure and shopping emotion pleasure fully mediated the relation between consumers perceptions on store atmosphere and impulse buying.